Women with osteoporosis present Their quality of life: Three cases from Vlore, Albania - Fatjona Kamberi; Yllka Stramarko; Brunilda Subashi; Glodiana Sinanaj (Archives of Community Medicine and Public Health - Peertechz Publications, 2018)
Aim: Osteoporosis is a disease characterized by low bone mass and micro-architectural deterioration of bone tissue, with a consequent increase in bone fragility and increase to fracture risk. Around the world, up to one in three women and one in fi ve men are at risk of an osteoporotic fracture. Osteoporosis can be prevented and managed with healthy and balanced diet, rich in calcium and vitamin D, an exercise plan, a healthy lifestyle and regular medications. Our aim was to show what patients with osteoporosis, based in their experience with the disease suggest to do for better quality of life. Methods: In this study we are reporting two cases with osteoporosis and one with osteopenia. Based on qualitative research methods face-to-face semi-structured interviews were conducted. Patients included in the study were patients diagnosed with osteoporosis and randomly selected from medical records in the Primary Health Care Center, No 2 in the city of Vlora. We contact them by phone and once the overall purpose has been explained, they express eligibility to be part of the study. Results: This study shows how the disease history was, what where the factors and barriers forsuccess in the self-management of osteoporosis and the preventive measures for osteoporosis in caseof osteopenia. These cases report how osteoporosis progresses silently and can have a severe impact on the health and well-being of those who suffer from it, especially if it is not diagnosed and treated in a timely manner.